Reconfigurable Supply Chains and Industry 4.0: Drivers of Enhanced Performance - Acevedo-Amaya, Mario Roberto; Ortega-Jimenez, Cesar H.; Rivera-Alvarado, Raul Enrique (LACCEI, 2025)
The Fourth Industrial Revolution has driven the adoption of Industry 4.0 (I4.0) in supply chains (SCs), enhancing agility, flexibility, transparency, and competitiveness while fostering Reconfigurable Supply Chains (RECs). However, the role of I4.0 in improving the supply chain (SC) and company performance (PERF) remains unclear. Using hierarchical regression analysis and a multiple mediation model with a sample of 309 international firms, we demonstrate that RECs are primarily cost-oriented, rather than structurally reconfigurable, with only six REC enablers significantly impacting performance. The results show that I4.0 fully mediates the relationship between REC and SC performance (SCP) and partially mediates the SCP-PERF link. Thus, I4.0 is evolving from a mediator to a potential moderator in the SCP-PERF relationship.